ANALYSIS OF THE EFFECTS OF INFLATION, INTEREST RATES AND FINANCING EXCHANGE RATES: THIRD-PARTY FUNDS AS A VARIABLE OF ISLAMIC BANKING INTERVENTION IN INDONESIA - Yanto, Nanang Ari; Rosmanidar, Elyanti; Nengsih, Titin Agustin; Usdeldi, Usdeldi; Laila, Umi Muzakiyatuk (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
The purpose of this study is to understand how inflation as measured through consumer price indices, interest rates, and exchange rates affects financing obtained from third-party funds in Islamic Banking in Indonesia. This research takes place in a quantitative framework and applies path analysis as a data processing technique. The data used is secondary in the form of a time series, including total financing, mudharabah financing, musyarakah financing, murabahah financing, as well as third-party fund variables, inflation, interest rates, and exchange rates. Data processing is carried out using the Eviews version 12 application. The findings of this study indicate that inflation affects total financing, mudharabah financing, musyarakah financing, while not impacting murabahah financing and third-party funds. In contrast, interest rates have no effect on total financing and third-party funds. The exchange rate also has no impact on third-party funds. Third-party funds show a positive influence but have no impact on financing. The results of the path analysis show that third-party funds do not function as mediators between total financing, mudharabah financing, musharakah financing, and murabahah financing.